ACSM's health/fitness facility standards and guidelines - Tharrett, Stephen J.; Peterson, James A. (Illinois : Human Kinetics, 2012)
ACSM's Health/Fitness Facility Standards and Guidelines, Fourth Edition, presents the current standards and guidelines that help health and fitness establishments provide high-quality service and program offerings within a safe and appropriate environment.
Chapter 1 : Pre-Activity Screening -- Chapter 2 : Orientation, Education, and Supervision -- Chapter 3 : Risk Management and Emergency Policies -- Chapter 4 : Professional Staff and Independent Contractors Standards for Health/Fitness Facilities -- Chapter 5 : Health/Fitness Facility Operating Practices -- Chapter 6 Health/Fitness Facility Design and Construction -- Chapter 7 : Health/Fitness Facility Equipment -- Chapter 8 Signage in Health/Fitness Facilities
Includes bibliographical references and index.
Keywords: SPORTS FACILITIES -- STANDARDS -- UNITED STATES; PHYSICAL FITNESS CENTERS -- STANDARDS -- UNITED STATES